2010
DOI: 10.1063/1.3496625
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-induced change in the electrical properties of metal-insulator-semiconductor Pt–GaN diodes

Abstract: Exposure of Pt-SiO 2 -GaN diodes to hydrogen at room temperature is found to change the conduction mechanisms from Fowler-Nordheim tunneling to Pool-Frenkel emission. The capacitance-voltage ͑C-V͒ curve for Pt-SiO 2 -GaN diodes in hydrogen significantly shifts toward negative bias values as compared with that in nitrogen. In sharp contrast, Pt-Si x N y -GaN diodes exhibit Pool-Frenkel emission in nitrogen and do not show any change in the conduction mechanism upon exposure to hydrogen. The C-V curve for Pt-Si … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…As a result, the barrier height of Schottky contacts is apparently reduced upon exposure to hydrogen. As for Pt-SiO 2 -GaN MIS diodes, it was reported that exposure of the devices to hydrogen was found to change the conduction mechanisms from Fowler-Nordheim tunneling to Poole-Frenkel emission [ 7 ]. According to first-principles calculations of hydrogen-induced defect energy levels in SiO 2 using a DFT method, K. Xiong et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the barrier height of Schottky contacts is apparently reduced upon exposure to hydrogen. As for Pt-SiO 2 -GaN MIS diodes, it was reported that exposure of the devices to hydrogen was found to change the conduction mechanisms from Fowler-Nordheim tunneling to Poole-Frenkel emission [ 7 ]. According to first-principles calculations of hydrogen-induced defect energy levels in SiO 2 using a DFT method, K. Xiong et al .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is important to investigate the hydrogen response mechanism of Pd-MOS devices in order not only to improve the hydrogen sensors but also to secure the reliability of electronic devices. As another example which shows that the change in the catalytic metal work function is not the dominant factor for hydrogen sensitivity, there is a literature which reports hydrogen responses of MIS Pt-GaN diodes with both SiO 2 and Si x N y dielectrics [ 7 ]. In the report, the characterized devices are completely identical structure except for the dielectrics between the Pt and the GaN.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported the critical role of the dielectric layer between the Schottky metal and the GaN surface in hydrogen sensitivity of devices [1622]. In this report, firstly, hydrogen sensing characteristics of Pt–GaN Schottky diodes fabricated on intentionally defect-introduced GaN surfaces are investigated.…”
Section: Resultsmentioning
confidence: 99%
“…For GaN Schottky diode-type hydrogen sensors, it was reported that an oxidic intermediate layer between the catalytic Schottky contact and the GaN surface is the origin of the hydrogen sensitivity of Pd–GaN Schottky diodes, implying that the metal /semiconductor interfacial modification would lead to significant change in the interaction of hydrogen with devices [ 15 ]. Several authors have reported the critical role of the dielectric layer between the Schottky metal and the GaN surface in hydrogen sensitivity of devices [ 16 22 ]. In this report, firstly, hydrogen sensing characteristics of Pt–GaN Schottky diodes fabricated on intentionally defect-introduced GaN surfaces are investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation